Longitudinal Analysis of Relationship between Entrepreneurial Mindset Skills Training and Entrepreneurial Knowledge Improvement among Adolescent Girls and Young Women in South Africa - Jean Damascene Mvunabandi; Ferina Marimuthu; Haruna Maama (Universitas Proklamasi 45, 2022)
Motivated by the lack of empirical research on entrepreneurial mindset knowledge training among adolescent girls and young women (AGYW) in South Africa, this article examined the entrepreneurial knowledge among 3584 adolescent girls and young women from four provinces, i.e. KwaZulu Natal, Mpumalanga, Eastern Cape and Western Cape in South Africa. The article also assessed how entrepreneurial mindset and skills training could drive the development and growth of AGYWs' mindsets towards entrepreneurship and link them with employment entrepreneurship opportunities. This study adopted quantitative and descriptive research approaches via longitudinal data collection. Secondary data collected using a questionnaire survey during entrepreneurial mindset and skills training from July-October 2021 by the large anonymized not-for-profit organization in South Africa was used for data analysis. Robustness analysis was performed using descriptive statistics using SPSS version 27.0. The findings from the empirical part of this research proved that adolescent girls and young women significantly improved their knowledge entrepreneurially throughout the training. This article contributes to the current body of knowledge as it filled in the gap and contributed significantly to the entrepreneurial mindset skill and knowledge improvement among adolescent girls and young women in South Africa.